5g+9=-11

Simple and best practice solution for 5g+9=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5g+9=-11 equation:


Simplifying
5g + 9 = -11

Reorder the terms:
9 + 5g = -11

Solving
9 + 5g = -11

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 5g = -11 + -9

Combine like terms: 9 + -9 = 0
0 + 5g = -11 + -9
5g = -11 + -9

Combine like terms: -11 + -9 = -20
5g = -20

Divide each side by '5'.
g = -4

Simplifying
g = -4

See similar equations:

| 4x+7=4x+1 | | 2x+219=525 | | 3x-8=328 | | 8.8t-9=7.8t-9 | | (x-6)(x-12)(x-18)=0 | | 4x+44=8x+8 | | x/3+3/7=7/9 | | 12(z+4)-4(z-1)=3(z-3)+4(z-1) | | (15-2x)(10-2x)=0 | | 19x-(2x-3)=88 | | 15-2x+10-2x=0 | | 5(4x-8)-2=5(x-3)+78 | | 7x-(5x+8)=3x-43 | | 15+16x=45+8x | | 5(u-5)+9=2(u+4) | | x(3x-9)=(3x+7)(x-3) | | x(3x-9)=(3x+7)(x-3) | | 4x+22=6x+4 | | 9x^2+4y^2=25 | | -16a^6+8a^5-4a^4= | | f(x)=5*2.5x^2 | | 3a+2a=5a-24 | | 2x+(2x+1)=3 | | 2x-27=x+3 | | 6.4e+8= | | 6+0.10x=10 | | 10x+25=50 | | (10x)x(10y)= | | 2-3(2x+7)=-8+5x | | -3(6y-7)-y=-2(y-3) | | 23+18v=-21+14 | | 16y-15y=-5+5 |

Equations solver categories